PRODUCTION, PURIFICATION AND DETERMINATION MOLECULAR WEIGHT OF COAGULASE ENZYME FROM STAPHYLOCOCCUS AUREUS ISOLATED FROM CLINICAL SAMPLES - AL_ shimmery, Marwa Ali Athab; Authman, Sawsan Hassan; Abo Ksou, Mohammed Fadhil (Journal of Medical Genetics and Clinical Biology, 2024)
Background: Coagulase is a critical enzyme produced by pathogenic strains of Staphylococcus aureus, which plays a significant role in the classification of staphylococci into coagulase-positive (CoP) and coagulase-negative staphylococci (CoNS). This enzyme interacts with prothrombin to induce blood clotting, which is essential for understanding its pathogenic mechanisms. Knowledge Gap: Despite its importance, detailed methods for extracting, purifying, and characterizing coagulase from clinical S. aureus isolates remain underexplored, particularly in relation to optimizing purification conditions and accurately determining its molecular weight. Aims: This study aimed to extract and purify coagulase from Staphylococcus aureus isolated from clinical samples and to determine the enzyme's molecular weight using SDS-PAGE. Methods: A total of 2,000 clinical samples were collected from hospitals in Baghdad, yielding 130 isolates of S. aureus. The optimum conditions for coagulase production were identified as pH 7.5 and 37°C. Coagulase was extracted and purified through ammonium sulfate precipitation (50-80% saturation), SDS-PAGE, ion exchange chromatography with DEAE cellulose, and gel filtration using Sephadex G150. Results: The crude coagulase extract exhibited an activity of 1.7 U/ml. Following purification, the enzyme's specific activity was measured, and the molecular weight of the coagulase was determined to be 36 kilodaltons (kDa). Novelty and Implications: This study provides a detailed protocol for the extraction and purification of coagulase from clinical isolates of S. aureus, along with the molecular weight determination of the enzyme. The findings enhance the understanding of coagulase's biochemical properties and its role in staphylococcal pathogenicity, potentially contributing to improved diagnostic and therapeutic strategies.